Plasma Osteopontin in Acute Liver Failure - Srungaram, Praveen (Cytokine, 2015)
BACKGROUND: Osteopontin (OPN) is a novel phosphoglycoprotein expressed in Kupffer cells that plays a pivotal role in activating natural killer cells, neutrophils and macrophages. Measuring plasma OPN levels in patients with acute liver failure (ALF) might provide insights into OPN function in the setting of massive hepatocyte injury. METHODS: OPN levels were measured using a Quantikine® ELISA assay on plasma from 105 consecutive ALF patients enrolled by the US Acute Liver Failure Study Group, as well as controls including 40 with rheumatoid arthritis (RA) and 35 healthy subjects both before, and 1 and 3 days after undergoing spine fusion (SF) surgery as a model for acute inflammation. RESULTS: Median plasma OPN levels across all etiologies of ALF patients were elevated 10- to 30-fold: overall median 1055 ng/mL; range: 33 – 19127), when compared to healthy controls (median in pre-SF patients: 41 ng/mL; range 2.6 – 86.4). RA and SF post op patients had elevated OPN levels (37 ng/mL and 198 ng/mL respectively), well below those of the ALF patients. Median OPN levels were highest in acetaminophen (3603 ng/mL) and ischemia-related ALF (4102 ng/mL) as opposed to viral hepatitis (706 ng/mL), drug-induced liver injury (353 ng/mL) or autoimmune hepatitis (436 ng/mL), correlating with the degree of hepatocellular damage, as reflected by aminotransferase values (R value: 0.47 for AST, p < 0.001). CONCLUSIONS: OPN levels appeared to correlate with degree of liver necrosis in ALF. Very high levels were associated with hyperacute injury and good outcomes. Whether OPN exerts a protective effect in limiting disease progression in this setting remains uncertain.